Analysis of Mali's Economic Policy - DIAWARA Daman-Guilé; BALLO Amidou (International Journal of Scientific Research and Innovative Studies, 2025)
The analysis of Mali's economic policy since its independence in 1960 highlights a complex evolution marked by strategic choices, reforms, and crises. The country has experienced several phases, ranging from a socialist model to liberal reforms, followed by a transition to a market economy. Hence, the present study: Analysis of Mali's Economic Policy. Economic policy plays a crucial role in a country's development by stimulating economic growth, reducing poverty and inequalities, and ensuring economic stability. It also promotes sustainable development, strengthens infrastructure, attracts foreign investments, and enhances the competitiveness of local businesses. By integrating social and environmental considerations, it contributes to stronger social cohesion. Mali recorded an average growth of 3.5% between 2015 and 2022, with a strong dependence on gold, which represents 70% of its exports. The unemployment rate is around 7% of the active population, with a majority working in the informal sector, often without social protection. The structural reforms of the 1980s and 1990s allowed for partial liberalization, increasing the production of crops such as cotton. However, these changes have also exacerbated economic inequalities. Agriculture, accounting for 30% of GDP, remains vulnerable to climate and infrastructure challenges, although cotton production reached 800,000 tons in 2021. Corruption, with an index of 33/100 in 2021, constitutes a major obstacle to the effectiveness of economic policies. Political instability, notably the coup d'état in 2012, has had devastating economic consequences, increasing poverty and affecting key sectors. Mali must move towards sustainable development initiatives, particularly in renewable energy, with 200 MW of installed solar energy. Strengthening governance is crucial to improving transparency and accountability, involving local actors and civil society more actively.In summary, while Mali has made progress in some areas, it must overcome significant challenges to ensure inclusive and sustainable economic development. An integrated approach focused on sustainability and good governance will be essential to build a stable and prosperous economic future. Keywords : "Economic Policy, Crises, Unemployment; Population ; Dependence; Instability. Received Date: August 21, 2025 Accepted Date: September 13, 2025 Published Date: October 01, 2025 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/464